2020
DOI: 10.25289/ml.2020.9.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Post-acne Erythema Successfully Treated with 595-nm Picosecond-domain Neodymium:Yttrium-aluminum-garnet Laser

Abstract: Post-acne erythema (PAE) is one of the major problems during or after treatment of acne vulgaris with any modality. A variety of therapeutic options have been described with various clinical outcomes and side effects. We report here on treating a patient with PAE using 595-nm picosecond-domain neodymium:yttrium-aluminum-garnet (Nd:YAG) laser. After four sessions of treatment, the patient displayed nearly complete improvement and no remarkable adverse effects. To the best of the authors' knowledge, this is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…In addition, another theory is that PAE is caused by exogenous stimuli such as topical agents. 16 In this study, we found that light and laser-based devices were the most frequently used treatments for PAE. Generally, pulsed-dye lasers, which are non-ablative lasers, were the most commonly used laser devices for PAE.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In addition, another theory is that PAE is caused by exogenous stimuli such as topical agents. 16 In this study, we found that light and laser-based devices were the most frequently used treatments for PAE. Generally, pulsed-dye lasers, which are non-ablative lasers, were the most commonly used laser devices for PAE.…”
Section: Discussionmentioning
confidence: 80%
“…To half and each half randomly Received treatment with 577-nm HOPSL treatment (QuadroStar PRO ™ , Asclepion Laser Technologies) using the scanner handpiece, 1 mm spot size, 80% coverage, 12-15 J/cm 2 , 30 ms, 2 passes or no treatment Wen et al 11 A randomized split-face, investigatorblinded study 2020 16 Not reported III-V Each participants' face was divided to two sides. One side was treated with a 755 nm picosecond alexandrite laser with a fixed spot size of 6 mm, fluence of 0.71 J/cm 2 , pulse repetition of 5 Hz, and two to three passes were applied.…”
Section: Iii-v Patients Face Was Dividedmentioning
confidence: 99%
See 1 more Smart Citation
“…Several vascular laser treatments were tried over the past few years in the treatment of PAE such as pulsed dye laser, 7 Low-Fluence 585 nm Q-Switched Nd:YAG Laser, 1 picosecond alexandrite laser, 8 577 nm pro-yellow laser 9 and with 595-nm Picosecond-domain ND-YAG Laser. 10 Also, other procedures such as intense pulsed light therapy 10 and fractional radiofrequency micro needling. 3 other lasers like 589/1319 laser system have proven good results in treatment of acne and post acne.…”
Section: Introductionmentioning
confidence: 99%
“…Several vascular laser treatments were tried over the past few years in the treatment of PAE such as pulsed dye laser, 7 Low‐Fluence 585 nm Q‐Switched Nd:YAG Laser, 1 picosecond alexandrite laser, 8 577 nm pro‐yellow laser 9 and with 595‐nm Picosecond‐domain ND‐YAG Laser 10 …”
Section: Introductionmentioning
confidence: 99%